Teaching the brain to read : strategies for improving fluency, vocabulary, and comprehension - Willis, Judy. (Alexandria, Va. : Association for Supervision and Curriculum Development, 2008)
Get to the heart of teaching your students the reading process with this guide to what happens in the human brain when students learn how to read. Neurologist and middle school teacher Judy Willis connects classroom practice to the neurology of reading and provides whole-class and individualized activities, lessons, and units that you can use in every grade and subject to help all students become better readers.
From syllable to synapse: prereading through decoding -- Patterning strategies for brain compatible reading instruction -- Fluency building from the brain to the book -- Eliminating barriers on the road to fluency -- Vocabulary building and keeping -- Guiding the brain for successful reading comprehension.
Includes bibliographical references and index.
Print version record.
Added to collection customer.56279.3
Keywords: Reading; Reading -- Physiological aspects; Brain; Reading; Brain; Lecture; Lecture -- Aspect physiologique; Cerveau; brains; LANGUAGE ARTS & DISCIPLINES -- Reading Skills; Brain; Reading; Reading -- Physiological aspects